A, The Development of Chemistry Practical Module on Reaction Rate Material Based on Green Chemistry Oriented PBL - Solfarina Solfarina; Irhamni Irhamni; Rahadatul Aisy (FKIP University of Mataram, 2026)
This study aims to determine the validity or and feasibility of the results of student questionnaire responses to the chemistry practicum module on the reaction rate material that has been created. This study uses the ADDIE development model with the stages of analysis, design, development, implementation, and evaluation. This practicum module has been validated by 7 media and material experts with the condition that Vcount ≥ Vtable (Vtable = 0.82). The validity results obtained from media experts were 0.91, and the validity of material experts was 0.94, which can be stated as